Muhammadiyah Madiun City’s Communication Strategy in Utilizing Digital Spaces - Muhammad Syarifuddin syarif; Muhammad Mochtar Mas’od; Muh Niam (Institut Karya Mulia Bangsa, 2025)
The rapid development of digital communication technologies has transformed the ways organizations interact with the public, including religious organizations. Digital space is no longer merely a medium for information dissemination but has become a strategic arena for organizational communication, identity construction, and public engagement. This study aims to analyze the communication strategies employed by Muhammadiyah of Madiun City in utilizing digital space as part of its organizational and da‘wah activities. This research adopts a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, non-participant observation, and documentation of digital content managed by Muhammadiyah of Madiun City. Informants were selected purposively based on their involvement and authority in managing the organization’s digital communication. Data were analyzed using an interactive qualitative analysis model, emphasizing perspectives of organizational communication and digital communication. The findings indicate that Muhammadiyah of Madiun City has implemented an integrated digital communication strategy consisting of four main components: institutional informative communication, production and distribution of visual and audio-visual content, message adaptation based on Wasathiyah (Islamic moderation) values, and audience interaction and engagement strategies. Institutional informative communication strengthens transparency, accountability, and organizational credibility, while visual and audio-visual content enhances message attractiveness and outreach. Message adaptation based on Wasathiyah values reflects a value-based communication approach that promotes moderation, inclusivity, and contextual relevance. Meanwhile, engagement strategies foster dialogical communication and audience participation in the digital space. this study demonstrates that Muhammadiyah’s digital communication practices represent an integration of organizational governance, Islamic values, and digital media strategies, positioning the organization as adaptive and relevant within contemporary digital society.